A Concept for Predicting Occupants' Long-Term Visual Comfort within Daylit Spaces. Issue 4 (1st October 2016) - Jakubiec, J. Alstan; Reinhart, Christoph F.
ABSTRACT: A new visual comfort concept is introduced to describe the long-term visual impression of space occupants. This concept, in contrast to instantaneous assessment of visual comfort, aims to describe an overall rating of visual quality in a space. A paired study consisting of occupant surveys and detailed 6-minute time step visual comfort simulations was performed for the studio spaces of Gund Hall in Cambridge, Massachusetts, which is occupied by approximately 500 students. Occupants reported four primary ways of experiencing visual discomfort: discomfort glare, insufficient monitor contrast, direct visibility of the sun, and direct sunlight on the workplane. Survey results were located spatially and in terms of orientation within Gund Hall, and a simulation model was calibrated based on furniture layout, measured material reflectances, and local measured weather data. The results of the study illustrate that it is possible to use current simulation-based visual comfort predictions to predict occupants' long-term visual comfort assessments in a complex daylit space. By classifying occupant responses into two broad groupings of comfortable and uncomfortable, the prediction methodology correctly identifies reported comfort or discomfort from 73.2% to 86.5% of cases depending on time of day; however, more research is required for broader application of the long-term visual comfort model to other buildings. Through a spatial and temporal presentation of the simulation data, this new methodology can be used as feedback during the process of designing daylit spaces, avoiding visual discomfort, and increasing satisfaction within the built environment.